(untitled) (Global Journal of Human-Social Science, 2012)
Women make up 52 of our country s population Women have an important role in building up the contemporary Society but the socio-economic status of women is very poor rated Government is trying to change this scenario by implementation of several schemes like Swashakti Swadhar Swayam siddha Swayamsiddha is the scheme of socio-economic upliftment of rural women It has been started by department of Women Child Development in year 2001 Swayamsiddha worked in the rural routs by the help of Self Help Group SHG model of microfinance Swayamsiddha has been covered 650 Blocks of all states of the country The first phase of scheme is completed recently